Design of a Custom Tool Storage Rack Based on 5S Principles - Nur Hazirah Esmayatim; Rahim Jamian (Progress in Engineering Application and Technology, 2026)
The practice of 5S (Sort, Set in Order, Shine, Standardize, Sustain) improves productivity, but tool storage in machining workshops remains inefficient due to large tool inventories and limited space, leading to misplaced tools, inconsistent storage practices, and retrieval delays, where adding storage alone does not solve monitoring gaps. This project aims to design a 5S-based custom tool storage rack for a machining workshop in Universiti Tun Hussein Onn Malaysia (UTHM) Pagoh branch campus, enhanced with quick response (QR) code tracking for tool identification and Google Teachable Machine (GTM) AI image recognition for placement verification. A three-dimensional (3D) of computer aided design (CAD) model was developed using SolidWorks, focusing on labeled compartments and standardized placement zones. The audits of 5S showed full compliance for Sort, Set in Order, Shine, and Standardize, while Sustain was partial due to user adherence. The QR improved traceability and reduced loss, and GTM achieved high accuracy in detecting tool presence and correct placement under controlled conditions. Findings confirm that the principles of 5S, integrated with QR and AI enhances workshop tool management efficiency.